Tests for qualitative features in the random coefficients model - Fabian Dunker; Konstantin Eckle; Katharina Proksch; Johannes Schmidt-Hieber (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
The random coeffcients model is an extension of the linear regression model which allows for additional heterogeneity in the population by modeling the regression coeffcients as random variables. Given data from this model, the statistical challenge is to recover information about the joint density of the random coefficients which is a multivariate and ill-posed problem. Because of the curse of dimensionality and the ill-posedness, pointwise nonparametric estimation of the joint density is difficult and suffers from slow convergence rates. Larger features, such as an increase of the density along some direction or a well-accentuated mode can, however, be much easier detected from data by means of statistical tests. In this article, we follow this strategy and construct tests and confidence statements for qualitative features of the joint density, such as increases, decreases and modes. We propose a multiple testing approach based on aggregating single tests which are designed to extract shape information on fixed scales and directions. Using recent tools for Gaussian approximations of multivariate empirical processes, we derive expressions for the critical value. We apply our method to simulated and real data.
Keywords: 330; random coeffients model; Radon transform; ill-posed problems; Gaussian approximation; mode detection; monotonicity; multiscale statistics; shape constraints